(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Elderly individuals commonly experience interconnected health issues such as diminished sleep quality, decreased independence, and heightened fall risk—conditions frequently linked to metabolic dysregulation and sedentary lifestyles. This community service program was implemented in Abianbase Village, Gianyar, to promote elderly well-being through a combination of weekly physical exercise, monthly nutritional education, and routine health monitoring. A total of 150 elderly residents participated in the program’s initial phase, which included group exercise sessions, interactive health education, and clinical screening of blood pressure, glucose, and uric acid levels. Baseline health data revealed prevalent hypertension and impaired glucose regulation, emphasizing the importance of accessible community-based preventive services. The enthusiastic participation and positive engagement indicated strong community acceptance. This integrated model demonstrates a practical and sustainable approach to enhancing elderly health and may serve as a reference for similar programs in other community settings.